Cells : - Prescott, David M (Jones and Bartlett, 1988)
The book is organized into 16 chapiters, corresponding to the 16 chapiters in Cells. Each chapiter contains six sections: Chapiter summary, definition of bold-faced terms, drill questions, answers to the drill questions, thought questions and references for additional reading